Deleuze y la inversión del kantismo - Pachilla, Pablo (2018)
“Deleuze and the Inversion of Kantism”. In this paper we aim to look into French philosopher Gilles Deleuze’s work in order to see whether there is such a thing as a ‘reversal of Kantianism’, parallel to his more well-known reversal of Platonism. To this end, we will propose, firstly, to read in the key of reversal the movements made by Deleuze regarding intensity and extension, on the one hand, and the paradox of inner sense, on the other. Then, we will analyze why Kant had already accomplished two great reversals, regarding the classical conception of both time and law, and consequently, we will develop the Deleuzean conception of Nietzschean eternal return as a simultaneous reversal of both aspects. Finally, we will inquire about the tropos of the aforementioned reversal, calling on the concepts of humor and irony.